Technological Gap in Adoption of Recommended Wheat Production Practices - S.N. Soni, S.S. Thakur (Indian Journal of Extension Education, 2022)
Wheat is the main rabi crop growing in Vindhyan Plateau of Madhya Pradesh and Sehore is one of the major wheat growing area in the plateau. The technological development in agriculture increased the production and productivity but the impact of improved wheat production practices has not been so prominent in some area of Madhya Pradesh particularly in traditional practicing areas. In wheat growing area of Madhya Pradesh the technological change have been found in wide scale but the growth of wheat production in wheat growing area has been very slow mainly due to traditional nature of farming dominated by rainfed wheat production situation resulted very low level of productivity. With the introduction of high yielding and improved variety and use of adequate fertilizer, plant protection measure and irrigation, repeatedly, It was noted that there is a yield gap between tradition farmer’s production practices and improved production practices. Many research results stated that if such yields could be realized by all the farmers then the present level of wheat production can be increased by more than 30 per cent, which indicated the magnitude of un-harvested yield that it still there in the wheat growing area. Keeping the view as importance, the present study was carried out to estimate the technological gap in wheat production and to examinethe relationship between technological adoption and different interrelated socio personal, socio-physiological and socio economic factors at the existing level of resources in wheat production